Geweld in de polder - Rooy, P. de (BMGN - Low Countries Historical Review, 2004)
Violence in the polders There is a staunch Whig tradition in Dutch historiography coupled with a strong inclination to emphasize moderation and tolerance as key features in Dutch history. The explanation for the relatively low level of violence, however, is rather weak or missing altogether. This article presents a case that links the low level of violence to three positive factors: the Netherlands was situated, geopolitically speaking, in the eye of the storm; there were relatively few cases of famine; and, it had no iron and coal basins that could easily be exploited. Violence, therefore, tended to manifest itself in the form of strict social control: specifically developed through the process of keeping tight control of religious differences, which culminated in the system of pillarization in the nineteenth century and continued as a means of suppressing the class war. This throws some light on one specific aspect of modern Dutch history, namely that far from being weak (as maintained in the Whig tradition), the state and societal organizations strengthened each other, as a result of which they were able to dispel all manner of unrest and discontent.